Syncline in interbedded sandstones and shales - Wojtal, Steven F. (Oberlin College Library, 1981)
At left is an open anticline whose hinge surface dips moderately to the left (east); its nearly horizontal left (eastern) limb is cut by a normal fault. To the right (west) is a tight syncline-anticline pair with nearly vertical hinge surfaces.